Design and Development of a Fullstack Information System for an E-Flight Ticket Platform Using JavaScript (JESII: Journal of Elektronik Sistem InformasI, 2023)
Whatever the reason for people's craving for speed, air travel in the present day is developing quite quickly. Online transportation service providers are starting to appear in response to the growing demand for air travel, catering to consumers' desires for convenience and speed. As time went on, the public's enthusiasm in making online travel reservations led to the establishment of an increasingly well-liked e-ticket platform. This study aims to design and develop a Fullstack E-Flight Ticket Platform information system that uses primarily Javascript programming language. The information system is designed to simplify the process of order flight tickets online, starting from scheduling search, route selection, payment, to sending electronic tickets to customers. In this research, users requirement and comprehensive system design were carried out using UML and Entity Relationship Diagram (ERD). The development of this information system uses Javascript libraries, such as Node.js, React.js, and ExpressJS. The result of this research is a Fullstack E-Flight Ticket Platform information system that run well and can be easily, intuitive users experiences. With the Fullstack E-Flight Ticket Platform information system, it is hoped that it can simplify and speed up the process of ordering flight tickets for the people of Indonesia and also become a reference for researchers or information system developers in developing fullstack Javascript-based information systems.